Learn about texture - Law, Felicia (U.K : World Books, 1992)
Poldy and his friends visits Signora Pittipatti's restaurant. Here they feat on a selection of leftover food which Signora Pittipatti offers them.
Keywords: Texture -- Fiction; Children stories